Effect of Supplementing Eucalyptus (Eucalyptus globulus) Leaf Powder on Average Weekly Feed Intake and Egg production of Commercial Laying Hens (Indian Journal of Animal Production and Management, 2024)
The present experiment was designed to study the effect of dietary incorporation of eucalyptus leaf  powder on the average weekly feed intake and egg production of commercial laying hens. A 12-week  feeding experiment was conducted on 72 White Leghorn laying chickens of 28 weeks of age. Hens  were randomly assigned to one of four treatment groups, each having 18 birds and three replicates  of six birds. Four treatments were included as a control (T1): basal diet, (T2): Incorporation of 0.3%  eucalyptus leaf powder in the basal diet containing phytase, (T3): Incorporation of 0.45% eucalyptus  leaf powder in the basal diet containing phytase, (T4): incorporation of 0. 6% eucalyptus leaf powder  in the basal diet containing phytase. Daily feed intake and egg production were recorded. The results  revealed that Supplementing Eucalyptus (Eucalyptus Globulus) Leaf powder did not affect the  cumulative performance of laying hens in terms of feed intake and egg production (P>0.05). Based  on the above findings, it was determined that adding 0.3 percent eucalyptus leaf powder to the basal  diet containing phytase improves egg production. Furthermore, because Eucalyptus leaves can be  procured at no cost, their incorporation is cost-effective and can help reduce feed expenditures.
Keywords: Egg production; Eucalyptus leaf powder; Feed intake; Laying hens; Performance